ACE- inhibitory and antioxidant activities in probiotic Cheddar cheese incorporated with Inulin and Whey Protein Concentrate - Luhana , Anjani B. (Indian Journal of Dairy Science, 2023)
The aim of this study was to compare angiotensin-converting enzyme (ACE) - inhibitory and antioxidant activities of Cheddar and probiotic Cheddar cheese using Lactobacillus plantarum DSM 20174 with inulin and whey protein concentrate (WPC). Water soluble extracts (WSE)  of probiotic Cheddar cheese exhibited higher ACE-inhibitory activity than their Cheddar cheese counterparts. A similar trend was observed for antioxidant activity. The highest antioxidant activity (2183.55 μM of Trolox) was obtained when cheese supplemented with WPC and probiotic (PCW) after 6 months of ripening among all the samples  followed by probiotic cheese with inulin (PCI). Similarly, PCW had highest ACE- inhibitory activity (88.51%) after 6 months of ripening. The electrophoretic and RP-HPLC profiles indicated that the rate of degradation of proteins resulted in formation of smaller peptides  were highest in PCW followed by PCI among all the samples. The results suggest the potential use of WPC in presence of L. plantarum DSM 20174 for production of Cheddar cheese enhanced ACE-inhibitory and antioxidant properties.